Operating Profitability of For-Profit and Not-for-Profit Florida Community Hospitals During Medicare Policy Changes, 2000 to 2010 - Barbara Langland-Orban PhD; John T. Large PhD; Alan M. Sear PhD; Hanze Zhang MSPH; Nanhua Zhang PhD (SAGE Publishing, 2015)
Medicare Advantage was implemented in 2004 and the Recovery Audit Contractor (RAC) program was implemented in Florida during 2005. Both increase surveillance of medical necessity and deny payments for improper admissions. The purpose of the present study was to determine their potential impact on for-profit (FP) and not-for-profit (NFP) hospital operating margins in Florida. FP hospitals were expected to be more adversely affected as admissions growth has been one strategy to improve stock performance, which is not a consideration at NFPs. This study analyzed Florida community hospitals from 2000 through 2010, assessing changes in pre-tax operating margin (PTOM). Florida Agency for Health Care Administration data were analyzed for 104 community hospitals (62 FPs and 42 NFPs). Academic, public, and small hospitals were excluded. A mixed-effects model was used to assess the association of RAC implementation, organizational and payer type variables, and ownership interaction effects on PTOM. FP hospitals began the period with a higher average PTOM, but converged with NFPs during the study period. The average Medicare Advantage effect was not significant for either ownership type. The magnitude of the RAC variable was significantly negative for average PTOM at FPs (−4.68) and positive at NFPs (0.08), meaning RAC was associated with decreasing PTOM at FP hospitals only. RAC complements other Medicare surveillance systems that detect medically unnecessary admissions, coding errors, fraud, and abuse. Since its implementation in Florida, average FP and NFP operating margins have been similar, such that the higher margins reported for FP hospitals in the 1990s are no longer evident.